(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article explores the nuanced utilization of political and social texts as pedagogical tools in teaching foreign languages to aspiring journalists. The discussion emphasizes the significance of contextual relevance, critical analysis, and language proficiency development within journalistic education. Practical implications, teaching methodologies, and the impact on students’ linguistic and socio-political awareness are examined.